ASSOCIATION BETWEEN ARECA NUT CHEWING HABIT WITH CARIES AND ORAL HYGIENE STATUS IN YPK GETSEMANI ELEMENTARY STUDENTS RAJA AMPAT REGION - RIEUWPASSA, IRENE E.; FAHRUDDIN, ANDI MUH; TATENGKENG, FRANSISKE (International Journal of Applied Pharmaceutics, 2019)
Objective: Areca nut is the most commonly used substance abuse in the world after tobacco, alcohol and caffeine. In Indonesia, the habit of chewing areca nut quid has been consuming most people in the eastern region such as Maluku and Papua. Areca nut (Areca catechu) can prevent caries because it has antiseptic properties derived from the content of selenium, tannins and alkaloids. In addition, the formed stain acts as a physical barrier on demineralizing the email. Knowing the dental and oral hygiene’s score is important for each individual, it plays a role in preventing the occurrence of caries. Oral hygiene status and caries can be assessed using the OHI-S and def-t index according to WHO. Methods: This is observational analytic research using a cross-sectional design. Samples are 4th, 5th and 6th grade (aged 8-13 y) students of YPK Getsemani Elementary School, Raja Ampat Regency with total sample number of 50 students. The results were analyzed using SPSS 20 program. Results: This study indicates 20% caries prevalence, based on WHO category is moderate and def-t averages was 0.46 in the WHO category is very low. Based on chi-square test results obtained p<0.05, indicating that there is a significant association between the frequency of areca nut chewing with caries status. Conclusion: Caries status in areca nut chewer is very low and there is a significant association between the frequency of areca nut chewing with caries status on children.